2002
DOI: 10.1002/1521-3994(200210)323:5<453::aid-asna453>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We present spot models for nine years of continuous VIc photometry of UZ Lib from 1993–2001. The relatively stable double‐humped light curve shape suggests extreme phase coherence. From the spot‐modelling analysis, we found that the major spots or spot groups are always located on the hemisphere facing the secondary star and exactly in the opposite hemisphere anti‐facing the secondary. Several single‐humped light curves and our suggested binary scenario rule out a pure ellipsoidal variability as the cause of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 13 publications
4
31
0
Order By: Relevance
“…On the other hand, long-term photometric observations exist for a much wider sample of spotted stars in binary systems (e.g., Strassmeier et al 1997Strassmeier et al , 2011Oláh & Strassmeier 2002;Oláh et al 2003Oláh et al , 2013Lindborg et al 2013, etc. ), which can also be used for investigating the role of binarity in the formation of magnetic activity.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, long-term photometric observations exist for a much wider sample of spotted stars in binary systems (e.g., Strassmeier et al 1997Strassmeier et al , 2011Oláh & Strassmeier 2002;Oláh et al 2003Oláh et al , 2013Lindborg et al 2013, etc. ), which can also be used for investigating the role of binarity in the formation of magnetic activity.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the long-term cyclic variability of UZ Lib (Oláh et al 2002b) has practically no effect in the rotational regime of the Fourier spectrum. We find that using the dataset pre-whitened with the short frequencies or just as observed give the same results well within the errors.…”
Section: Data Methods and Numerical Simulationsmentioning
confidence: 98%
“…Its overall data quality is near 5 mmag in V over the course of its operation (for details of the data see Oláh et al 2002b); this V dataset was used in the present paper.…”
Section: Data Methods and Numerical Simulationsmentioning
confidence: 99%
“…Such a phenomenon has been noticed using the technique of Doppler imaging on, e.g., the active giant DM UMa (Hatzes 1995), on the two mainsequence components of σ 2 CrB (Strassmeier & Rice 2003), on the two pre-main sequence components of V824 Ara and the active giant UZ Lib (Oláh & Strassmeier 2002), as well as by long-term photometric analysis on, e.g., RT Lac (Ç akırlı et al 2003), UZ Lib (Oláh et al 2002a) and on the RS CVn stars II Peg, σ Gem and HR 7275 ). Holzwarth & Schüssler (2003) presented a numerical investigation for fast-rotating solar-like binaries which showed that, although the magnitude of tidal effects is small, they nevertheless lead to the formation of clusters of flux tube eruptions at preferred longitudes on opposite hemispheres and synchronized with the orbital motion.…”
Section: Preferred Longitudesmentioning
confidence: 90%